Menguatkan Spiritualitas Generasi Alpha Melalui Pendidikan Agama Kristen Yang Kontekstual - Legi, Hendrik; Legi, Devarsh Gevariel Dean (Sekolah Tinggi Agama Kristen Diaspora, 2025)
The Alpha Generation is a generation born in the digital era with very wide and fast access to information. However, the main challenge faced by this generation is the weakness of spirituality due to the dominance of technology in daily life. Christian religious education as part of character and faith formation has an important role in strengthening the spirituality of the Alpha generation. This article aims to examine how contextual Christian religious education can strengthen the spirituality of the Alpha generation. The method used in this study is a literature study with a qualitative approach. Data is collected through scientific literature, books, research articles, and relevant online sources. The analysis was carried out using the content analysis method to identify important themes related to spirituality and Christian education in the context of the Alpha generation. The results of the study show that contextual Christian religious education is able to answer the challenges of the spirituality of the Alpha generation by integrating the principles of the Christian faith into the digital context. This involves the use of digital media as a means of spiritual learning as well as a pedagogical approach that is interactive and relevant to the daily life of the Alpha generation. Christian religious education needs to prioritize the formation of character based on biblical values, such as love, loyalty, and integrity, while still considering the wise use of technology. This article concludes that strengthening the spirituality of the Alpha generation through contextual Christian religious education requires a dynamic, contextual, and technology-based approach. Thus, the Alpha generation can grow spiritually despite being in a challenging digital world. The recommendation for educators is to continue to develop creative and innovative learning strategies so that spirituality development remains relevant and effective.AbstrakGenerasi Alpha merupakan generasi yang lahir dalam era digital dengan akses informasi yang sangat luas dan cepat. Namun, tantangan utama yang dihadapi oleh generasi ini adalah lemahnya spiritualitas akibat dominasi teknologi dalam kehidupan sehari-hari. Pendidikan Agama Kristen sebagai bagian dari pembentukan karakter dan iman memiliki peran penting dalam menguatkan spiritualitas generasi Alpha. Artikel ini bertujuan untuk mengkaji bagaimana pendidikan agama Kristen yang kontekstual dapat menguatkan spiritualitas generasi Alpha. Metode yang digunakan dalam penelitian ini adalah studi pustaka dengan pendekatan kualitatif. Data dikumpulkan melalui literatur ilmiah, buku, artikel penelitian, dan sumber daring yang relevan. Analisis dilakukan dengan metode analisis isi (content analysis) untuk mengidentifikasi tema-tema penting terkait spiritualitas dan pendidikan Kristen dalam konteks generasi Alpha. Hasil penelitian menunjukkan bahwa pendidikan agama Kristen yang kontekstual mampu menjawab tantangan spiritualitas generasi Alpha dengan mengintegrasikan prinsip-prinsip iman Kristen ke dalam konteks digital. Hal ini melibatkan pemanfaatan media digital sebagai sarana pembelajaran rohani serta pendekatan pedagogis yang interaktif dan relevan dengan kehidupan sehari-hari generasi Alpha. Pendidikan agama Kristen perlu mengedepankan pembentukan karakter berbasis nilai alkitabiah, seperti kasih, kesetiaan, dan integritas, dengan tetap mempertimbangkan penggunaan teknologi secara bijaksana. Artikel ini menyimpulkan bahwa penguatan spiritualitas generasi Alpha melalui pendidikan agama Kristen yang kontekstual membutuhkan pendekatan yang dinamis, kontekstual, dan berbasis teknologi.